Congenital pineoblastoma and parameningeal rhabdomyosarcoma: concurrent two embryonal tumors in a young infant - (:unkn) unknown (SPRINGER, 2006)
Background: Pineoblastomas are very rare brain tumors in fetus and neonates, comprising only 0.9% of congenital brain tumors. The occurrence of multiple tumors of different histopathologic types in the same individual is a rare event, most often encountered in hereditary cancer syndromes. Case report: We report a female fetus presented with a congenital pineoblastoma at the 32nd week of gestation, with hydrocephalus and concurrent parameningeal embryonal rhabdomyosarcoma in early infancy. Results: Cytogenetic analysis showed normal karyotype in the peripheral blood of the patient, and p53 mutational analysis revealed no germ line mutations. Discussion: This is the first case with concurrent congenital pineoblastoma and parameningeal embryonal rhabdomyosarcoma in early infancy. We suggest that concurrence of these tumors could be due to mutations in other tumor suppressor genes or secondary to exposure to unknown in utero factors.
Keywords: brain tumor; congenital; pineoblastoma; rhabdomyosarcoma; p53 gene mutation; PERINATAL BRAIN-TUMORS; TERATOMA; PINEAL; ASTROCYTOMA; MUTATION; CHILDREN; PATIENT